Degradation of trimethoprim by gamma irradiation in the presence of persulfate. (October 2016) - Zhang, Zhonglei; Yang, Qi; Wang, Jianlong
Abstract: The degradation and mineralization of trimethoprim (TMP) by gamma irradiation was investigated in the presence of persulfate (PS). The TMP was degraded at initial concentration of 20 mg/L in aqueous solution with addition of 0, 0.5, 1, 1.5, 2 mM persulfate respectively. The effect of pH values (6.5, 7.5 and 8.5) on TMP degradation was also determined. The experimental results showed that the degradation and mineralization of TMP could be significantly enhanced by persulfate at acidic condition (pH=6.5). Several intermediate products generated during gamma irradiation process through hydroxylation, demethylation and cleavage were identified using liquid chromatography with tandem mass spectrometry (HPLC-MS). The degradation pathway of TMP was tentatively proposed based on the identification of intermediate products. Highlights: Trimethoprim (TMP) degradation by gamma irradiation was investigated. Persulfate significantly enhanced TMP degradation. The effect of pH values (6.5, 7.5 and 8.5) on TMP degradation was determined. The possible degradation pathway of TMP was tentatively proposed.